(untitled) (International Journal of Engineering and Computer Science, 2015)
The communication through water is different scenario from the communication on the land, while transmission through the water the delays are frequently happens when the signals received from geographically separated nodes. Moreover, UWA communications enable high motion agility and flexibility of the nodes, and allow interactive system query and instantaneous system response. The UWA environment is commonly viewed as one of the most challenging environments for wireless communications and networking. It differs from the terrestrial radio environment in many different aspects. Although tremendous progress has been made in the past literature but still the synchronism issues is concerned area in the field of UWA communications. To resolve the issue of the synchronism issues usage of the OFDM communication system is employed and transmissions at the source node by preceding every OFDM block with an extremely long cyclic prefix (CP) which reduces the transmission rates dramatically. One may increase the OFDM block length accordingly to compensate for the rate loss which also degrades the performance due to the significantly time-varying nature of UWA channels. In this paper, we develop a new OFDM-based scheme to combat the asynchronism problem in cooperative UWA systems without adding a long CP (in the order of the long relative delays) at the transmitter. By adding a much more manageable (short) CP at the source, we obtain a delay diversity structure at the destination for effective processing and exploitation of spatial diversity by utilizing a low complexity Viterbi decoder at the destination, e.g., for a binary phase shift keying (BPSK) modulated system, we need a two-state Viterbi decoder. We provide pair wise error probability (PEP) analysis of the system for both time-invariant and block fading channels showing that the system achieves full spatial diversity. Finally the simulation results shows that performance of the proposed method is good over the conventional state of the art methods and extensive simulations that the proposed scheme offers a significantly improved error rate performance for time-varying channels (typical in UWA communications) compared to the existing approaches.